2020
DOI: 10.21203/rs.3.rs-20335/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combination Therapy with Pemafibrate (K-877) and Pitavastatin Improves Vascular Endothelial Dysfunction in Dahl/Salt-sensitive Rats Fed a High-salt and High-fat Diet​

Abstract: Background: Statins suppress the progression of atherosclerosis by reducing low-density lipoprotein (LDL) cholesterol levels. Pemafibrate (K-877), a novel selective peroxisome proliferator-activated receptor α modulator, is expected to reduce residual risk factors including high triglycerides (TGs) and low high-density lipoprotein (HDL) cholesterol during statin treatment. However, it is not known if statin therapy with add-on pemafibrate improves the progression of atherosclerosis. The aim of this study was t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…In fact, several previous studies demonstrated that an increase in serum levels of TG may be associated with an increased risk of the development of retinopathies 113–115 . Based on our present and previous data as well as others, oral administrations of pemafibrate showed strong reducing effects on serum TG levels 18,20,46,116,117 . In this regard, oral administrations of pemafibrate could effectively reduce the risk of the development and/or progression of retinopathies in humans.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In fact, several previous studies demonstrated that an increase in serum levels of TG may be associated with an increased risk of the development of retinopathies 113–115 . Based on our present and previous data as well as others, oral administrations of pemafibrate showed strong reducing effects on serum TG levels 18,20,46,116,117 . In this regard, oral administrations of pemafibrate could effectively reduce the risk of the development and/or progression of retinopathies in humans.…”
Section: Discussionsupporting
confidence: 80%
“…To manage retinal degeneration caused by retinal I/R injury, pemafibrate was orally administered to adult mice daily according to the timeline of the experiments (Figure 1A). The dose of pemafibrate was determined based on previous administration protocols 20,23,45,46 . Retinal I/R injury was induced in mice 4 days after oral administration of pemafibrate.…”
Section: Resultsmentioning
confidence: 99%
“…The beneficial effect of fenofibrate on the prognosis of DMT2 patients and dyslipidemia was also confirmed by Koopal et al In a study involving 17,142 patients from the FIELD (the Fenofibrate Intervention and Event Lowering in Diabetes), ACCORD (the Action to Control Cardiovascular Risk in Diabetes), and SMART (Second Manifestations of ARTerial disease) studies [61]. Unfortunately, the Pemafibrate to Reduce Cardiovascular OutcoMes by Reducing Triglycerides IN patiENts With diabeTes (PROMINENT) phase 3 study with pemafibrate was prematurely discontinued (April 2022) due to the unlikely achievement of the primary endpoint [62][63][64]. The REDUCE-IT (Reduction of Cardiovascular Events With Icosapent Ethyl-Intervention Trial) showed that the use of icosapent ethyl (IPE) in patients with high TG and diabetes type 2 led to a reduction risk of CV death, nonfatal myocardial infarction, nonfatal stroke, coronary revascularization, or unstable angina by 25% (HR = 0.77; 95% CI: 0.68-0.87).…”
Section: Effective Reduction Of Triglyceride Rich Lipoproteinsmentioning
confidence: 99%
“…Previous randomized clinical trial demonstrated that pitavastatin 4 mg compared with pitavastatin 1 mg therapy significantly reduced LDL-C and clinical outcomes irrespective of renal function state [ 10 ]. When used in combination, pitavastatin and pemafibrate improved lipid profile and endothelial function in hypertension and insulin resistance model rats [ 11 ]. Ihm et al also reported combination therapy with pitavastatin and fenofibrate more effectively reduced non-HDL-C compared with pitavastatin monotherapy in patients with a high risk for cardiovascular disease [ 12 ].…”
Section: Introductionmentioning
confidence: 99%